The Effect of Academic Qualifications, Work Experience and Work Motivation on the Performance of Principal School in Sub-District Rupat Bengkalis Regency - Mardianawati Mardianawati; Caska Caska; Sumarno Wati Sumarno (Journal of Educational Sciences, 2022)
The Principal of the State Elementary School in the Rupat District, Bengkalis Regency, had 32 strata 1 academic qualifications and 1 master's degree. However, temporary observations show signs that the academic qualifications of the principals who are not suitable show variations in their performance. The type of research carried out is survey research with a quantitative research approach. The location where this research was conducted is in Rupat District, Bengkalis Regency, Riau Province. The population of this study were principals of public elementary schools, totaling 37 people. In this study, researchers used a saturated sample. So the sample of this study amounted to 37 people. The results of this study shows there is a significant influence between academic qualifications on the performance of principals in SDS in Rupat District. The magnitude of the effect is 0.601 or 60.1%. There is also a significant influence between work experience on the principal's performance in SDS in Rupat District with the magnitude of the effect is 0.463. The last is there is a significant influence between work motivation on the principal's performance as well in SDS Rupat District.